Pharmacokinetics Alterations in Critically Ill Pediatric Patients on Extracorporeal Membrane Oxygenation: A Systematic Review - Sutiman, Natalia; Koh, Janine Cynthia; Watt, Kevin; Hornik, Christoph; Murphy, Beverly; Chan, Yoke Hwee; Lee, Jan Hau (Frontiers in Pediatrics, 2020)
OBJECTIVES: To identify alterations in pharmacokinetics in children on extracorporeal membrane oxygenation (ECMO), identify knowledge gaps and inform future pharmacology studies. DATA SOURCES: We systematically searched the following databases from earliest publication until November 2018: MEDLINE, CINAHL and EMBASE, using a controlled vocabulary and keywords related to: “ECMO”, and “pharmacokinetics”, “pharmacology”, “drug disposition”, “dosing” and “pediatrics”. STUDY SELECTION: Inclusion criteria were: study population aged <18 years, supported on ECMO for any indications, receiving any medications while on ECMO and reported pharmacokinetics data. DATA EXTRACTION: Clearance and/or volume of distribution (Vd) values were extracted from included studies. DATA SYNTHESIS: 41 studies (total patients=574) evaluating 23 drugs met the inclusion criteria. The most common drugs studied were anti-microbials (n=13), and anticonvulsants (n=3). 28 studies (68%) were conducted in children < 1 year of age. 33 studies (80%) were conducted without intra-study comparisons to non-ECMO controls. Increase in volume of distribution attributable to ECMO was demonstrated for 9 (56%) drugs: cefotaxime, gentamicin, piperacillin/tazobactam, fluconazole, micafungin, levetiracetam, clonidine, midazolam and sildenafil (range: 23-345% increase relative to non-ECMO controls), which may suggest the need for higher initial dosing. Decreased volume of distribution was reported for 2 drugs: acyclovir and ribavirin (50 and 69%, respectively). Decreased clearance was reported for gentamicin, ticarcillin/clavulanate, bumetanide and ranitidine (range: 26-95% decrease relative to non-ECMO controls). Increased clearance was reported for caspofungin, micafungin, clonidine, midazolam, morphine and sildenafil (range: 25-455% increase relative to non-ECMO controls). CONCLUSIONS: There were substantial pharmacokinetic alterations in 70% of drugs studied in children on ECMO. However, studies evaluating pharmacokinetic changes of many drug classes, and those that allow direct comparisons between ECMO and non-ECMO patients, are still lacking. Systematic evaluation of pharmacokinetic alterations of drugs on ECMO that incorporate multi-drug opportunistic trials, physiologically based pharmacokinetic modeling, and other methods are necessary for definitive dose recommendations. TRIAL REGISTRATION PROSPERO Identifier: CRD42019114881